2010
DOI: 10.1007/s00264-010-1091-8
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic compression with foot pumps facilitates early postoperative mobilisation in total knee arthroplasty

Abstract: Deep-vein thrombosis (DVT) and pulmonary embolism (PE) represent life-threatening postoperative complications frequently responsible for in-hospital mortality following total knee arthroplasty (TKA). Mechanical prophylaxis in the form of a foot pump offers an alternative to pharmacological and physical therapy. The aim of this prospective and randomised study was to examine the clinical efficacy of the A-V Impulse (AVI) system in reduction of soft-tissue swelling of the lower limb following a TKA. A total of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Of these, 6 were observational studies [29][30][31][32][33][34] and 41 were RCTs. Twenty-one studies included patients undergoing hip arthroplasty, 20 included those undergoing knee arthroplasty, 29,30,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]75 and 6 included both. [31][32][33][34]73,74 More than 1 prophylactic drug was used in several studies (eg, case group using pentassacharide and control group using enoxaparin).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 6 were observational studies [29][30][31][32][33][34] and 41 were RCTs. Twenty-one studies included patients undergoing hip arthroplasty, 20 included those undergoing knee arthroplasty, 29,30,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]75 and 6 included both. [31][32][33][34]73,74 More than 1 prophylactic drug was used in several studies (eg, case group using pentassacharide and control group using enoxaparin).…”
Section: Resultsmentioning
confidence: 99%
“…The 47 studies recruited 44 844 patients (21 369 undergoing TPHA and 23 475 undergoing TPKA). eTables 2-4 summarize, respectively, the characteristics of the 21 TPHA studies, the 20 TPKA studies, 29,30,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]75 and the 6 studies for both TPHA and TPKA, [31][32][33][34]73,74 which reported 443 cases of symptomatic postoperative VTE that occurred between surgery and patient hospital discharge, 288 in the patients undergoing knee arthroplasty and 155 in those undergoing hip arthroplasty. Of these cases, 275 were DVT (182 in the TPKA group and 93 in the TPHA group) and 149 were pulmonary embolism (106 in the TPKA group and 43 in the TPHA group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering extremity surgery, manual lymphatic drainage is broadly accepted for the treatment of postoperative and posttraumatic oedema [31][32][33] as well as oedema caused by other pathologies [2,29,30], even though corresponding evidence is conflicting [3,4,34,35]. The application of pneumatic compression was also established as treatment option [36][37][38], although again with limited evidence base [38][39][40][41]. Kinesiotaping might be yet another approach for the treatment of oedema.…”
Section: The Broader Contextmentioning
confidence: 99%
“…Conversely, studies have shown no differences in VTE rates when foot pumps were added compared to chemoprophylaxis alone, but this has only been reported following THA [54,[56][57][58][59]. A single institution prospective randomized clinical trial comparing foot pumps to LMWH found no difference in DVT incidence following THA at 6-day follow-up (18% versus 13%; P = 0.25) [54].…”
Section: Foot Pumpmentioning
confidence: 93%